2022
DOI: 10.4149/bll_2023_007
|View full text |Cite
|
Sign up to set email alerts
|

Choline and citicoline ameliorate oxidative stress in acute kidney injury in rats

Abstract: OBJECTIVES: The purpose of this study is to investigate the effects of cholinergic anti-infl ammatory pathway (CAP)-activating drugs, choline and citicoline (Cytidinediphosphate-choline, CDP-choline), on lipopolysaccharide (LPS)-induced acute kidney injury (AKI) parameters and the contribution of NADPH Oxidase4 (NOX4) p22phox. BACKGROUND: Endotoxemia induces a systemic infl ammatory response characterized by the production of pro-infl ammatory mediators and reactive oxygen species (ROS), which eventually devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Moreover, α7nAChR expression ACh levels, and choline acetyltransferase activity also decreased ( Han et al, 2018 ). We previously demonstrated the therapeutic efficacy of CAP-inducing agents, choline and CDP-choline, in mitigating LPS-induced elevations in ROS, TNFα, and NF-κB levels ( Baris et al, 2023b ). Studies performed on the effects of a 3-month smoking cessation program using varenicline on vascular function and oxidative stress markers showed that after 3 months, participants have decreased levels of carbon monoxide (CO), MDA, protein carbonyls (PC), and augmentation index (Aix), indicating reduced arterial stiffness and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, α7nAChR expression ACh levels, and choline acetyltransferase activity also decreased ( Han et al, 2018 ). We previously demonstrated the therapeutic efficacy of CAP-inducing agents, choline and CDP-choline, in mitigating LPS-induced elevations in ROS, TNFα, and NF-κB levels ( Baris et al, 2023b ). Studies performed on the effects of a 3-month smoking cessation program using varenicline on vascular function and oxidative stress markers showed that after 3 months, participants have decreased levels of carbon monoxide (CO), MDA, protein carbonyls (PC), and augmentation index (Aix), indicating reduced arterial stiffness and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-one metabolites in the YT extract-treated groups were significantly changed compared with those in the HFD group; the altered metabolite pathways included glycerol phospholipid metabolism, vitamin B6 metabolism, and nicotinate and nicotinamide metabolism, which supported the anti-obesity and lipid-lowering effect of YT extract. Metabolites such as citicholine, acetylcholine, pyridoxine, and NAD have been well reported on the regulation of obesity, dyslipidemia, infection, and oxidative stress ( 50 53 ). In the present study, correlation analysis between significantly changed metabolites and metabolic syndrome-related indices further demonstrated that YT extract administration was positively associated with weight loss, alleviation of inflammatory and oxidative stress, and lower hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%